Preliminary study on assessment and taxonomic status of pseudophyllinae bush-crikets (orthoptera:tettigoniidae) from Malaysia. - Muzamil .M,; Bakhtiar .E.Y,; Idris B.A, (Pusat Sistematik Serangga ,UKM, 2010)
This paper reports the preliminary finding on the assessment and taxonomic status of pseudphyllinae bush-crikets from Malaysia. A total of 61 species were recorded, of which 45 species belong to 21 genera are from Peninsular Malaysia, while 29 species belong to 17 genera are from Sabah and Sarawak. A list of pseudophyllinae bush-crikets from Malaysia is provided to highlight the records for both Peninsular Malaysia and Sabah and Sarawak.